let a=b therefore,ab=b^2 so we can say,,,,,,,,,,,,,,,ab -a^2= b^2-a^2 after factorization we get,,,,,,,,,,,,a(b-a)=(b-a)(b+a) therefore,,,,,,,,,a=a+b since a=b,,,,,,,,,,,,,,,,,,a=2a therefore 1=2

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestWell, it's same as cancelling zeroes on both sides, which is not allowed in mathematics!

Thus,

a(b-a) = (b-a)(b+a)

the above equation is same as:

a(0) = (0)(b+a)

Hence, it will be incorrect to slash off zeroes from both the sides!

Log in to reply

well done

Log in to reply

We can't cancel a-b from both sides without writing that a-b=0 can be a solution.

Log in to reply